دراسة التألق الحراري لمركبات السيراميك (Gd2O2S:Tb and Y2O2S:Tb) بتأثير أشعة (X ) (Latakia University Journal -Basic Sciences Series, 2018)
In this paper, we discuss the results of the luminescence properties of gadolinium and yttrium oxysulphides doped with terbium. These materials are known as effective X-ray screen phosphors. Their applications are more accessible in a ceramic form. The emission spectra of the Gd2O2S: Tb and Y2O2S: Tb show lines which are associated with 5D3 - 7FJ’ and 5D4 - 7FJ (J’ = 0-6, J = 1-6) transitions in terbium. The decay time of the luminescence of these oxysulphides was found to be 200 ms. We found that new defects in the samples appeared after the ceramic formation in comparison with the initial powders. Energy levels of the defects were estimated using thermostimulated luminescence (TSL) measurements. The determined characteristics (light yield, relative concentrations of traps, transparency, and afterglow) of studying ceramics, depend on the pressure conditions and a thermal treatment. The ceramics light yield, was almost the same as that of the powders, despite of the new defects presence. powders were obtained despite the presence of new defects.       The measurements have been held in Tech-governmental University of Petersburg-Petersburg-Russia. In year 2003           نبين في هذا البحث مميزات التألق لأكاسيد مركبات الأيتريوم والكادولينيوم مع التيربيوم. تتصف هذه المواد بأنها فوسفورية حاجزة فعالة للأشعة السينية، وتطبيقاتها أكثر قبولاً على شكل مركبات السيراميك. ينتج طيف الإصدار لهذه المركبات: (Gd2O2S:Tb and Y2O2S:Tb) عن الانتقالات بين سويات الطاقة لـ:  (5D3 –7FJ’ ) و(5D4 – 7FJ)، حيث (J’ = 0-6,J = 1-6) هي انتقالات طيف الأيتريوم. وجدنا أن زمن التضاؤل التألقي لمركبات الأكاسيد الكبريتية هذه يصل إلى  /200 ms/. تمت مقارنة أطياف هذه المركبات السيراميكية المشكلة مع أطيافها على شكل بودرة وإيجاد العيوب فيها. كذلك تم تقدير الخلل في سويات الطاقة باستخدام قياسات التألق الحراري التحفيزي (TSL).  تبين أن مميزات (مردود الإصدار الضوئي التركيب النسبي-الشفافية لما بعد التألق) للمركبات السيراميكية المدروسة تتعلق بشروط الضغط والمعالجة الحرارية. غير أن مردود الإصدار الضوئي للسيراميك والبودرة هو نفسه تقريباً بغض النظر عن وجود بعض العيوب الجديدة. أجريت القياسات التجريبية في جامعة بطرس بورغ التكنولوجية الحكومية – بطرس  بورغ –روسيا. عام(2003)